Reconstruction of the Concept of Nafkah in the Gig Economy Era: A Comparative Study on the Financial Responsibility of Husbands toward Wives and Children - Rohman, Miftakur; Asror, Ubainul; Khoir, Amirul (Sakina: Journal of Family Studies, 2026)
The rapid expansion of the gig economy has challenged the conventional foundations of family maintenance (nafkah) in Islamic family law, which traditionally presuppose stable employment and predictable income. Existing studies have extensively examined gig work from labor law and social protection perspectives, while Islamic family law scholarship remains largely detached from the realities of platform-mediated employment. Consequently, no comprehensive framework has been developed to address the implications of income volatility for maintenance obligations. This study aims to reconstruct the concept of nafkah by developing an Adaptive Nafkah framework that redefines the legal rationale (‘illat) of maintenance from fixed employment to productive capacity. Employing a comparative normative legal approach, the study analyzes maintenance regulations in Indonesia, the United States, and the United Kingdom through comparative functionalism and legal content analysis, complemented by a doctrinal examination of fiqh principles. The findings reveal that all three jurisdictions inadequately address the fluctuating income patterns characteristic of gig workers, resulting in significant legal uncertainty in maintenance determination. To overcome this limitation, the study proposes an Average Earning Algorithm (AEA) grounded in the fiqh maxim al-mashaqqah tajlib al-taysir, enabling maintenance obligations to be calculated according to actual earning capacity while preserving family welfare objectives. The proposed model provides a more adaptive, equitable, and legally coherent mechanism than conventional fixed-income approaches. This research contributes to the renewal of fiqh muamalah by introducing the Adaptive Nafkah theory, advances comparative family law through a functional bridge between Islamic and secular maintenance systems, and offers a practical framework for reforming maintenance adjudication in the era of digital labor markets. <!--a=1-->